Antibacterial and antibiofilm efficacy of repurposing drug hexestrol against methicillin-resistant Staphylococcus aureus - Shasha Liu; Pengfei She; Zehao Li; Yimin Li; Linhui Li; Yifan Yang; Linying Zhou; Yong Wu (Elsevier, 2023)
There has been an explosion in the prevalence of methicillin-resistant Staphylococcus aureus (MRSA) because of the indiscriminate use of antibiotics. In this study, we repurposed hexestrol (HXS) as an antibacterial agent to fight planktonic and biofilm-related MRSA infections. HXS is a nonsteroidal synthetic estrogen that targets estrogen receptors (ERα and ERβ) and has been used as a hormonal antineoplastic agent. In our work, the minimum inhibitory concentrations (MICs) were determined using the antimicrobial susceptibility of MSSA and MRSA strains. Anti-biofilm activity was evaluated using biofilm inhibition and eradication assays. Biofilm-related genes were analyzed with or without HXS treatment using RTqPCR analysis of S. aureus. HXS was tested using the checkerboard dilution assay to identify antibiotics that may have synergistic effects. Measurement of ATP and detection of ATPase allowed the determination of bacterial energy metabolism. As shown in the results, HXS showed effective antimicrobial activity against S. aureus, including both type strains and clinical isolations, with MICs of 16 µg/mL. Sub-HXS strongly inhibited the adhesion of S. aureus. The content of extracellular polymeric substances (EPS) and the relative transcription levels of eno, sacC, clfA, pls and fnbpB were reduced after HXS treatment. HXS showed antibacterial effects against S. aureus and synergistic activity with aminoglycosides by directly interfering with cellular energy metabolism. HXS inhibits adhesion and biofilm formation and eradicates biofilms formed by MRSA by reducing the expression of related genes. Furthermore, HXS increases the susceptibility of aminoglycosides against MRSA. In conclusion, HXS is a repurposed drug that may be a promising therapeutic option for MRSA infection.